Excavating hidden adsorption sites in metal-organic frameworks using rational defect engineering. Issue 1 (December 2017) - Chong, Sanggyu; Thiele, Günther; Kim, Jihan
Abstract Metal–organic frameworks are known to contain defects within their crystalline structures. Successful engineering of these defects can lead to modifications in material properties that can potentially improve the performance of many existing frameworks. Herein, we report the high-throughput computational screening of a large experimental metal–organic framework database to identify 13 frameworks that show significantly improved methane storage capacities with linker vacancy defects. The candidates are first identified by focusing on structures with methane-inaccessible pores blocked away from the main adsorption channels. Then, organic linkers of the candidate structures are judiciously replaced with appropriate modulators to emulate the presence of linker vacancies, resulting in the integration and utilization of the previously inaccessible pores. Grand canonical Monte Carlo simulations of defective candidate frameworks show significant enhancements in methane storage capacities, highlighting that rational defect engineering can be an effective method to significantly improve the performance of the existing metal–organic frameworks. Defects in metal-organic frameworks have an important impact on the properties of resultant materials. Here, based on computational screening the authors identify 13 frameworks that experience drastic improvements in their methane storage capacities upon introduction of linker vacancy defects.